2017
DOI: 10.1002/asia.201700348
|View full text |Cite
|
Sign up to set email alerts
|

Cimicifoetones A and B, Dimeric Prenylindole Alkaloids as Black Pigments of Cimicifuga foetida

Abstract: Two dimeric prenylindole alkaloids with a unique indole-benzoindolequinone skeleton, cimicifoetones A (1) and B (2), were isolated as black pigments from the rhizomes of Cimicifuga foetida. The structures were elucidated by spectroscopic methods including HRMS and 2D NMR, as well as single-crystal X-ray diffraction and computational chemical modeling techniques. Cimicifoetones A and B represented the first examples of dimeric indole alkaloids generated through [4+2] Diels-Alder cycloaddition between the prenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This bis-indole alkaloid, (3′R)-hydroxytaberanelegantine C, was isolated from the methanol extract of T. elegans roots and exhibited potent apoptosis induction activity, accompanied by the level of Bcl-2 and XIAP decreased in HCT116, SW620, and HepG2 cells [ 86 ]. Furthermore, cimicifoetones is a dimeric indole alkaloid derived from the rhizomes of Cimicifuga foetida, which could enhance the expression of caspase-3/-8/-9, promote the cleavage of PARP, downregulate the anti-apoptotic proteins, Bcl-2, Bcl-xL, and upregulate the pro-apoptotic protein Bax, indicating a simultaneous activation of both extrinsic and intrinsic apoptotic pathways in HL-60 cells [ 87 ]. Malsy et al found that staurosporine could induce apoptosis of pancreatic cancer cells through an intrinsic pathway, and the expression of anti-apoptotic factors Bcl-2 and Bad were reduced in PaTu 8988T cells, whereas staurosporine failed to induce apoptosis in colon cancer cells [ 88 ].…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
“…This bis-indole alkaloid, (3′R)-hydroxytaberanelegantine C, was isolated from the methanol extract of T. elegans roots and exhibited potent apoptosis induction activity, accompanied by the level of Bcl-2 and XIAP decreased in HCT116, SW620, and HepG2 cells [ 86 ]. Furthermore, cimicifoetones is a dimeric indole alkaloid derived from the rhizomes of Cimicifuga foetida, which could enhance the expression of caspase-3/-8/-9, promote the cleavage of PARP, downregulate the anti-apoptotic proteins, Bcl-2, Bcl-xL, and upregulate the pro-apoptotic protein Bax, indicating a simultaneous activation of both extrinsic and intrinsic apoptotic pathways in HL-60 cells [ 87 ]. Malsy et al found that staurosporine could induce apoptosis of pancreatic cancer cells through an intrinsic pathway, and the expression of anti-apoptotic factors Bcl-2 and Bad were reduced in PaTu 8988T cells, whereas staurosporine failed to induce apoptosis in colon cancer cells [ 88 ].…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
“…Two indole alkaloids (289 and 290) were separated from C. dahurica and inhibited soluble epoxide hydrolase in a dose-dependent manner [ 50 ]. Two dimeric prenylindole alkaloids, named cimicifoetone A and cimicifoetone B, could not only be used as black dyes but also remarkably repress cancer cells multiplication [ 51 ].…”
Section: Phytochemistrymentioning
confidence: 99%
“…Its most abundant profiles were triterpenes and phenolic acids , and the phenolic compounds were proven to be the most important contributors to the biological activity of Cimicifuga dahurica , such as anti‐cancer, antibacterial, and antioxidant . Previous researches indicated that Cimicifuga dahurica contains unique phenolic compounds, such as cimicifugic acid B, which have been proved to be significant biologically active compounds . As a result, the derivative of cimicifugic acid B have been paid more attention, such as chemical synthesis, anti‐HIV, and antioxidant activity .…”
Section: Introductionmentioning
confidence: 99%